2008
DOI: 10.1021/jf802158u
|View full text |Cite
|
Sign up to set email alerts
|

Water and Salt Distribution in Atlantic Salmon (Salmo salar) Studied by Low-Field 1H NMR, 1H and 23Na MRI and Light Microscopy: Effects of Raw Material Quality and Brine Salting

Abstract: The effect of different Atlantic salmon raw materials (prerigor, postrigor and frozen/thawed) on water mobility and salt uptake after brine salting was investigated by using LF 1H NMR T2 relaxation,1H and 23Na MRI and light microscopy. Distributed exponential analysis of the T2 relaxation data revealed two main water pools in all raw materials, T21 and T22, with relaxation times in the range of 20-100 ms and 100-300 ms, respectively. Raw material differences were reflected in the T2 relaxation data. Light micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
50
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 101 publications
(59 citation statements)
references
References 50 publications
9
50
0
Order By: Relevance
“…Most studies report 2-3 water populations in fish and meat muscle, depending on their proton relaxation properties (Jepsen et al 1999;Erikson et al 2004;Bertram and Andersen 2007;Bertram et al 2009;Aursand et al 2009). Bertram and Andersen (2007) and Bertram et al (2009) identified three water populations in pork at 1-3 ms (T 2B ), suggested to correspond to water closely associated with macromolecules and proteins, at 40-80 ms (T 21 ), suggested to correspond to myofibrillar water or water located within organized protein structures and at 200-400 ms (T 22 ) corresponding to extra-myofibrillar water.…”
Section: Low Field Nmr Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies report 2-3 water populations in fish and meat muscle, depending on their proton relaxation properties (Jepsen et al 1999;Erikson et al 2004;Bertram and Andersen 2007;Bertram et al 2009;Aursand et al 2009). Bertram and Andersen (2007) and Bertram et al (2009) identified three water populations in pork at 1-3 ms (T 2B ), suggested to correspond to water closely associated with macromolecules and proteins, at 40-80 ms (T 21 ), suggested to correspond to myofibrillar water or water located within organized protein structures and at 200-400 ms (T 22 ) corresponding to extra-myofibrillar water.…”
Section: Low Field Nmr Resultsmentioning
confidence: 99%
“…Transversal relaxation time measurement have shown to give strong correlations to various physicochemical properties of fish and meat muscle, such as moisture content (Andersen and Rinnan 2002), water holding capacities and drip loss (Jepsen et al 1999;Erikson et al 2004) and has been used to indicate pH-induced structural changes occurring in the muscle post mortem (Bertram et al 2000) as well as the effects of frozen storage on protein denaturation in fish (Steen and Lambelet 1997). The technique can give valuable information about the distribution of water throughout the muscle and how it is changed by various handling or processing (Jepsen et al 1999;Erikson et al 2004;Bertram and Andersen 2007;Bertram et al 2009;Aursand et al 2009) and is therefore an excellent technique for studies on the effects of protein injection to fish muscle.…”
Section: Introductionmentioning
confidence: 99%
“…If, for example, changes in muscle tissues would occur as a result of fish processing, this can be detected as changes in proton relaxation times (Erikson et al, 2004). A correlation between NMR relaxation times and light microscopy of salmon muscle has been described by Aursand et al (2009).…”
Section: Nmr Proton Relaxation Behaviormentioning
confidence: 99%
“…On the other hand, the extent of physical activity and psychological stress before the onset of death, and the cause of death itself, can also have an effect on the point in time of the onset, dissipation and intensity of rigor mortis (Dix and Graham 2000;Krompecher et al 1983;Perper 2006;Tornberg 1996). An increased strain on the muscles antemortem (whether illness or stress related, and whether in direct relation or without any relation to the cause of death) can, for example, accelerate the onset of rigor mortis (Aursand et al 2009;Clark et al 1997;Gill-King 1997;Kiessling et al 2006;Krompecher et al 1983;Robinson et al 1953;Roth et al 2006;Tornberg 1996).…”
Section: Rigor Mortismentioning
confidence: 99%